1996
DOI: 10.1063/1.117830
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling GaN quantum dots on AlxGa1−xN surfaces using a surfactant

Abstract: Nanoscale GaN quantum dots were fabricated on AlxGa1−xN layer surfaces via metalorganic chemical vapor deposition. In order to achieve a self-assembling dot structure, a two-dimensional growth mode (step flow) of GaN films on AlxGa1−xN (x=0–0.2) surfaces that is energetically commenced under the conventional growth conditions was intentionally modified into a three-dimensional mode by using a ‘‘surfactant.’’ The surfactant is believed to inhibit the GaN film from wetting the AlGaN surface due to the change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
160
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(162 citation statements)
references
References 0 publications
2
160
0
Order By: Relevance
“…As a possible origin, Ruminov et al suggested that Si mostly affects the dislocation structure during the GaN growth, perhaps by changing the atom mobility and the number of growth islands at the initial stage of the growth, and/or changing the dislocation mobility. Aoyagi and co-workers [23][24][25] have used the influence of silicon on the growth of GaN, InGaN, and AlGaN to grow quantum dots. In these studies it has been demostrated that silicon acts as a surfactant at the initial stages of growth, inducing a three-dimensional Stranski-Krastanow growth mode.…”
Section: Discussionmentioning
confidence: 99%
“…As a possible origin, Ruminov et al suggested that Si mostly affects the dislocation structure during the GaN growth, perhaps by changing the atom mobility and the number of growth islands at the initial stage of the growth, and/or changing the dislocation mobility. Aoyagi and co-workers [23][24][25] have used the influence of silicon on the growth of GaN, InGaN, and AlGaN to grow quantum dots. In these studies it has been demostrated that silicon acts as a surfactant at the initial stages of growth, inducing a three-dimensional Stranski-Krastanow growth mode.…”
Section: Discussionmentioning
confidence: 99%
“…al. [3], but in this case the growth, that was undertaken by CVD, was not controlled by an intrinsic SK mode, and the size of the dots was rather large (typically 40 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Such signatures are routinely analysed to support the identification of excitons and biexcitons in micro-photoluminescence (m-PL) spectroscopy 13,24,25 . However, for the majority of wurtzite c-plane GaN/AlN QDs 26,27 with diameters larger than E6 nm, this picture cannot be valid anymore for the following reasons. The strong internal piezo-and pyroelectric fields separate the electron-from the holesubsystem and cause a very distinct confinement in the growthdirection (c-axis) for both charge carrier types.…”
mentioning
confidence: 99%